Sweet corn crop response to different dripline spacings in the dry Mediterranean area - Ibrahim MUBARAK; Mussaddak JANAT (Acta Agriculturae Slovenica)
Increasing the spacing between driplines is the most significant factor in reducing the high initial costs of drip irrigation system. A two-year field study (2017 and 2018) was conducted on a clay loam soil to evaluate the effects of different dripline spacings (75, 150, 225, and 300 cm) on sweet corn yields, soil water status, and irrigation water use efficiency (IWUE) in the dry Mediterranean area. Results showed that the average husked cob yield (HCY) and IWUE were significantly decreased as the dripline spacing increased. HCY was 13.93, 12.30, 9.18, and 6.86 t ha-1, for dripline spacing of 75, 150, 225, and 300 cm, respectively, for an average irrigation water depth of 725 mm. Both soil water storages and yields decreased with distance from the dripline. The 150-, 225- and 300 cm dripline spacings yielded 11.7, 34.0 and 50.8 % less than the 75 cm dripline spacing, but these wider dripline spacings provided 50, 67 and 75 % less unit-area cost, respectively. However, these reductions in crop yield did not justify the extra cost of the closer dripline spacing, at low crop prices and high dripline costs. Finally, further studies are needed to benefit from the higher initial unit-area cost savings obtained under the wider dripline spacings.